Fluorescence Imaging of Posterior Spiracles from Second and Third Instars of Forensically Important Chrysomya rufifacies (Diptera: Calliphoridae)1, 2. Issue 6 (5th October 2016) - Flores, Danielle; Miller, Amy L.; Showman, Angelique; Tobita, Caitlyn; Shimoda, Lori M. N.; Sung, Carl; Stokes, Alexander J.; Tomberlin, Jeffrey K.; Carter, David O.; Turner, Helen
Abstract: Entomological protocols for aging blowfly (Diptera: Calliphoridae) larvae to estimate the time of colonization (TOC) are commonly used to assist in death investigations. While the methodologies for analyzing fly larvae differ, most rely on light microscopy, genetic analysis, or, more rarely, electron microscopy. This pilot study sought to improve resolution of larval stage in the forensically important blowfly Chrysomya rufifacies using high‐content fluorescence microscopy and biochemical measures of developmental marker proteins. We established fixation and mounting protocols, defined a set of measurable morphometric criteria and captured developmental transitions of 2nd instar to 3rd instar using both fluorescence microscopy and anti‐ecdysone receptor Western blot analysis. The data show that these instars can be distinguished on the basis of robust, nonbleaching, autofluorescence of larval posterior spiracles. High‐content imaging techniques using confocal microscopy, combined with morphometric and biochemical techniques, may therefore aid forensic entomologists in estimating TOC.